The advertisement call of Ameerega pulchripecta (Silverstone, 1976)(Anura, Dendrobatidae) - Costa-Campos, Carlos Eduardo; Lima, Albertina Pimentel; Amézquita, Adolfo (Zootaxa, 2016)
The name Ameerega picta was once used to denote a lineage of poison frogs (Dendrobatidae) distributed throughout most of the Amazon basin (Silverstone 1976); more recently, to describe a phenetic group involving at least 18 species, Lötters et al. (2007) pointed out that some of the lineages were indeed derived from the former A. picta. Among them, the nominal species with the widest distribution is A. hahneli (Haddad & Martins 1994; Twomey & Brown 2008), also an alleged complex of poorly defined species (Grant et al. 2006; Fouquet et al. 2007; Roberts et al. 2007). The mate-recognition signal, the advertisement call, was part of the evidence used to revalidate A. hahneli as a different species from A. picta. Although the advertisement call has been described for one or few individuals of other species in the group (Haddad & Martins 1994; Costa et al. 2006; Twomey & Brown 2008; Lötters et al. 2009), namely A. flavopicta, A. braccata and A. boehmei, and A. hahneli, we still lack a formal description for A. pulchripecta, the sister taxon of A. hahneli (Twomey & Brown 2008). Its call has been qualitatively described as similar to A. hahneli’s call, but “deeper-voiced” (Lötters et al. 2007).